2014
DOI: 10.1123/ijspp.2013-0119
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance and Impedance Vector Patterns as Predictors of League Level in Male Soccer Players

Abstract: In conclusion, soccer players belong to a specific population. Muscle mass and function, as indicated by BCM and phase angle, increase with increasing performance level. The soccer-specific tolerance ellipses might be used for classifying individual vectors and to define target regions for low-level players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
131
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(158 citation statements)
references
References 19 publications
20
131
1
1
Order By: Relevance
“…Furthermore, with increasing age and performance level of the athletes (Fig 3), a displacement to the left was also observed, due to a decrease in the R/h component in the absence of a difference in the Xc/h component. Other studies [15, 29, 47] have also reported vectors of sport samples shifted to the left when compared to their reference populations, which might reflect the specific adaptations of body composition in different sports [72]. Additionally, vectors shifted to the left have been reported with increasing age [15] and performance level [47] in sport samples.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, with increasing age and performance level of the athletes (Fig 3), a displacement to the left was also observed, due to a decrease in the R/h component in the absence of a difference in the Xc/h component. Other studies [15, 29, 47] have also reported vectors of sport samples shifted to the left when compared to their reference populations, which might reflect the specific adaptations of body composition in different sports [72]. Additionally, vectors shifted to the left have been reported with increasing age [15] and performance level [47] in sport samples.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies [15, 29, 47] have also reported vectors of sport samples shifted to the left when compared to their reference populations, which might reflect the specific adaptations of body composition in different sports [72]. Additionally, vectors shifted to the left have been reported with increasing age [15] and performance level [47] in sport samples. It remains to be investigated whether the differences are the result of vector displacement due to biological maturation, to the specific training process or a combination of both.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Con respecto a la BIA, el análisis de los vectores de impedancia es una herramienta que permite estudiar los cambios de la hidratación corporal y de la masa celular, sin la influencia del modelo matemático utilizado para estimar la composición corporal (18). Utilizando los vectores estimados a partir de las medidas físicas de la BIA, como la resistencia y la reactancia, normalizadas para la altura (19), se ha demostrado en jugadores de fútbol de élite que el acortamiento de estos vectores indica una desviación hacia elipses de mayor hidratación y masa celular (20). El desentrenamiento asociado a la ausencia de cargas de competición es una razón suficiente para provocar alteraciones de la CC susceptibles de ser evaluadas con precisión, por ejemplo, con la BIA; sin embargo, estas han sido poco estudiadas rigurosamente en jóvenes deportistas.…”
Section: Introductionunclassified